Work Facilities Improvement Using Systematic Layout Planning to Reduce the Risk of Manual Handling - Uswatun Khasanah; Auditya Purwandini Sutarto; Nailul Izzah (Journal of Novel Engineering Science and Technology, 2022)
Manual material handling (MMH) activity is considered a major ergonomic risk factor in Indonesian Small and Medium Enterprises (SMEs) that leads to the onset or development of musculoskeletal pain, particularly in the low back. It may exaggerate the risk of injury or disorders. This study evaluates the recommended weight limit (RWL) at UD Fatikh Sport, a SMES sports shoe manufacturer. In addition, we also propose a facility layout redesign to reduce the ergonomic risks of manual material handling activities. The NIOSH lifting equation was used to determine the RWL at four departments and during MMH activities. The Lifting Index (LI) of the MMH activity exceeded the recommended value, which might raise the ergonomic risks. The risks worsened because the operator carried the load manually to several departments, which were located separately on the second floor, without any aid tools. Two designs of facility layout improvement were developed using a systematic layout planning (SLP) approach. The first design was focused on minimizing the transportation distance, while the space requirement of each department or MMH activities was emphasized in the second design. It aims to improve working conditions and reduce workers' fatigue. Further research should calculate the productivity and estimate its cost-efficiency before and after implementing the proposed layout.